, My Heart’s in the Highlands…” Linguo-stylistic analysis of the poem (According to the original and translation - Rcheulishvili, Ia ("Intercultural Dialogues" Transactions, 2025)
The Scottish pre-Romantic poet Robert Berns holds an important place in the history of world literature. His poetry is multifaceted. We found it interesting to generalize the poetic techniques that made this poetry accessible and easily understandable to everyone. We chose the poem “My Hearts’s in the Highlands,..” by Robert Berns as a material for analyzing. The poem is dedicated to the native Scottish mountains. The poem with its spirit, reminded us of the poem by Ilia Chavchavadze , To Mountains of Kvareli”. Both of the poems express longing for the high mountains, where both the land and the air are pure. Observation has shown that the poem is rich in vocabulary, which is ensured by the distinctive stylistic devices used in it. We also found it interesting to study the Georgian translation of the poem. The translation preserves the rhythm, intonation and artistry of the poem. Therefore, we consider this translation to be a sample of translation that is closest to the original, very concise and at the same time graphic.